A fluence map optimization in IMRT for head and neck cancer based on trapezoidal fuzzy numbers* - ام البنین بزرگ; علیرضا فخارزاده جهرمی; علی دلاور خلفی (مدل‌سازی پیشرفته ریاضی)
The study of clinical observations in the family planning of intensity-modulated radiation therapy (IMRT), indicates that the target dose prescribed within the framework of trapezoidal fuzzy numbers, more closely matches the oncologist's goals. In this study, optimal treatment planning was described as a solution of an optimization problem using a quadratic objective function, where the prescribed target dose is a trapezoidal fuzzy number. First the problem was transformed into a non-fuzzy optimization problem, then the optimal solution was obtained based on the gradient method and projection operations. In this paper, we used Computational Entertainment for Radiotherapy Research (CERR) for treatment planning, importing the patient scans, and calculating the influence matrix. Numerical simulation was performed for a head and neck cancer case. Numerical results were presented in the form of Dose-Volume Histograms (DVH) and compared with the deterministic state. These results showed that the treatment planning that we provided based on the trapezoidal fuzzy target dose, is more consistent with the goals of oncologists.